Intrathecal injection of bone marrow concentrate in children with autism spectrum disorder: a retrospective chart analysis - Kobinia, Georg S.; Bukaty, Adam; Holly, Elisabeth; Kobinia, Gloria; Heuberer, Philipp R.; Laky, Brenda (Frontiers in Medicine, 2025)
BackgroundThe growing prevalence of autism spectrum disorder (ASD) underscores the urgent need for therapies that target underlying biological mechanisms, with cell-based interventions offering a potentially transformative approach by targeting core physiological disruptions rather than providing temporary symptom management. The purpose of this study was to report on our experience with an autologous cell-based intervention in children with ASD.MethodsThis retrospective data analysis included pre- and postinterventional data from 128 children with ASD who received intrathecal injections of autologous bone marrow concentrate. Patient and procedure related characteristics, complications, and the Autism Treatment Evaluation Checklist (ATEC) scores were extracted from patient's medical records.ResultsData were analyzed from 128 children (27 females and 101 males), aged between two and 16 years at their first intervention. A total of 32.8% underwent more than two single-step procedures. Significant improvements from the first to the second intervention were detected in the total and all subgroup ATEC scores, as well as in the severity groups (p < 0.001). Following the intervention, 4.6% of children transitioned from the “mild” or “moderate” to the “no symptoms” category, and 25.4% of the initially categorized “severe” group shifted to a milder symptom category. The average total ATEC score improved from the first to the second intervention by 19.0 ± 17.1 points, and one 60-point improvement was detected. The recorded ATEC score improvements in 85.9% of patients were similar between genders, as well as between age groups. A subgroup analysis of 39 patients who received three interventions also showed statistically significant differences in all ATEC scores between the three time points (p < 0.001). The highest improvements occurred after the first intervention, continued to improve over time, and remained reduced even three to four years after the intervention. There was not a single serious adverse event in the 307 treatments. All complications (e.g., nausea/vomiting) were resolved within a week or less after the procedure.ConclusionBoth a significant improvement in ATEC scores, and significant severity shifts to milder forms–even into the “no symptoms” category–suggest a measurable improvement in autism-related symptoms after autologous, bone marrow derived, intrathecally applied single procedures in children with ASD.